The Industrial Development Corporation's Distressed Funding: Effectiveness in rescuing distressed companies following the global financial crisis - Matlaila, Mamoekeng (Research of GSB, 2018)
The recent global financial crisis which began in the United States of America in 2007, spread to almost all economies in the world and evolved into a world economic downturn. Governments around the world introduced different rescue interventions to avoid the collapse of the financial and banking system and to stimulate economic growth. In addition to large scale economic stimulus packages, other forms of Government interventions were introduced in direct support of non-financial firms including Small and Medium Sized Enterprises (SMEs). These Government interventions have attracted little empirical attention with recent studies pointing out to the need for more evaluation of the impact of direct support interventions. This study attempts to contribute to the literature which focuses on the impact of interventions introduced by governments in developing countries, to resolve market failure in non-financial corporate companies as well as SMEs. This study is focused on assessing the effectiveness of the IDC distressed funding scheme in rescuing distressed companies in South Africa following the recent global financial crisis. We investigate the effects of the scheme on the financial performance of beneficiary companies. Our results show that overall the funding had a positive impact on beneficiary companies. The impact was greatest on the solvency, capital structure and leverage of the awarded companies. The funding was most effective in the first year following the injection of the capital into the business. The profitability and liquidity of the beneficiary company did not change significantly following accessing of the funding.